P. Dibeela, P. Lenka-Bula & V. Vellem (Eds.), Prophet from the South: Essays in honour of Allan Aubrey Boesak - Wessel Wessels (Acta Theologica)
From text: Allan Boesak emerged as a liberation theologian in 1976 after the publication of his doctoral thesis, Farewell to innocence. Since then, liberation theology guided his work in South Africa and abroad, in the church, and on public issues. Liberation theology enticed him to struggle against the injustices of both apartheid and democracy, albeit not without some mistakes. It is, therefore, no surprise that Boesak’s work had such an influence as to warrant not only a Festschrift, but such a global Festschrift as Prophet from the South. A quick overview of the list of contributors reveals Boesak’s influence, in the global North and the global South, on a diversity of people from all walks of life.